Have Australia's tourism strategies incorporated climate change?. Issue 5 (4th May 2018) - Moyle, Char-lee J.; Moyle, Brent D.; Chai, Andreas; Hales, Robert; Banhalmi-Zakar, Zsuzsa; Bec, Alexandra
ABSTRACT: Tourism is widely acknowledged as a key contributor to climate change, but it remains unclear how the tourism industry has been planning for climate change in practice. This paper conducts the most comprehensive critical review of Australia's tourism policy and planning documents to date. The paper explores the complex challenges posed by climate change to tourism and how tourism policy has been adapting over a 15-year period. Drawing on a longitudinal data-set of 477 Australian tourism policy and planning documents at the national, state, regional and local level, this research analyses the strategic discourse on climate change using content analysis and bibliometrics. The findings reveal opportunities, challenges and strategies for the tourism industry to contribute to the sustainable management of climate change. Opportunities include developing more "green" products, while strategies include establishing and/or participating in collaborative climate change schemes and strengthening dialogue surrounding climate change to aid the implementation of sustainable practices. Future research should consider the broader policy-making environment, such as the stakeholders, power and interest dynamics when analysing tourism strategies in relation to climate change.